Biography of a pseudonym: Suprakash Ray, Bengal (1915-1990) - Gangopadhyay, A (2018)
This thesis is a biography of an individual, Suprakash Ray. Born in the Borishal district of eastern Bengal in 1915/1918, he died in a hospital in Calcutta in 1990. Suprakash Ray was the most widely recognised of the many pseudonyms used by Sudhir Bhattacharya: the others were Bijan Sen and Kafi Khan. He was an anti-colonial terrorist as a teenager (1930s), a Communist partisan organiser in the tramworkers’ union in Calcutta (1930s and 1940s), and a history-teacher in a Calcutta school who split away from the Communist parties and wrote extensively on history and politics (1950s and 1960s). He had been sparsely mentioned in a few political and intellectual works. Beyond direct reference, his ideas and statements find solidarity in radical Communist partisans and platforms across twentieth century in the territory of the colonial and the Indian state and beyond. The primary thread emerging from this enquiry into his life and works is a largely suppressed truth – that there was a well-developed Communist thought of history and politics in this territory that was separate from Marxist historiography and political economy. This separation was an antagonistic procedure – where the Communist party leadership and centralised bureaucracy ratified Marxism as an evolutionary scheme which stifled subjective initiatives of ordinary partisans for immediate local application of the Communist programme or the egalitarian maxim. History of Communism in this territory is thus split into two. The leadership and party bureaucracy wanted to activate the absolute finitude of the Communist partisan in the face of the inexorable dual forces of history and (the Indian) state. The partisans were forced to embrace the role of conscience-keepers of planned industrial progress and parliamentary representative system initiated by the Indian state. The ordinary partisans affirmed the right to rebel against the colonial and the Indian state and wagered on infinity and immortality in the face of counter-revolutionary power. While the ordinary partisans declared the comprehensive possibility of a prospective metaphysics capable of enveloping present actions and drawing strength, in future, from what those actions would produce; the horizon of the party leadership was a greater technocratic role for Communists in the macroeconomic management of the lives of the citizens of India. The ordinary partisans were punished, excommunicated and criminalized by the leadership and the Indian state in equal measure. The ‘ordinary Communist partisan’ was a rare and obscure appearance, yet always consistent and self-declarative in broad sequences of time. Through Suprakash Ray – who thoughtfully designated himself as an ordinary Communist partisan rebelling against the leadership – we attempt to grasp the subjectivity of the ordinary Communist partisan. The extant literature on the history of Communism in the relevant territory pays scant attention to the internal registers, ideas and categories that subjectivated the Communist leadership and the ordinary partisans. A close and interiorised study of the statements and partisan political situations within which Suprakash Ray thought and acted can begin reversing such condescension where inventive subjects are invisibilised under the towering careers of the state, nation, society, culture and economy. Biography here becomes a microhistorical enterprise of apprehending singularity without flinching, without taming it and recombining it with the history of structures. The core contention of this thesis is that a biography can be written in interiority, there can be a thought of subjectivity in subjectivity. A basic survey of the philosophy of individuation indicates that a biography need not be an additive, epistemological or critical project. But what follows is also not entirely exegetical. The politics and the thought of history Ray upheld also featured in consistent and collective wagers of armed squads, local governments of liberated zones, partisans, platforms, partisan editorial collectives, thinkers, writers and empathisers in and around the Communist parties in the territory of the colonial and Indian state. The partisan universalism of Ray’s thought demands and ekes out for itself evident and difficult solidarity (with statements of ordinary partisans) – and equally evident, non-negotiable antagonism (with the Communist leadership’s statements). A specific use of previously unused party documents, letters, programmes, publications, avant garde literary and theoretical tracts and some academic works stabilise, unpack and oppose the stands and decisions of Ray throughout the thesis. A curated genealogy of such documents is presented in the bibliography. This literature is particularly complex. The leadership deserted Communist categories in its discourse with the Indian state and its citizens. But it did indeed retain those categories while dealing with inquisitive or recalcitrant ordinary party members. In other cases – the ‘Communist’ epithet was used to distinguish the Communist parties from other statist parties committed to the Indian state and its parliamentary elections, while the ordinary partisans were dissuaded by using the language of general history and structures. The attention towards Suprakash Ray’s statements and deployed categories leads to a new (in terms of the extant secondary literature on history of Communism in the relevant territory) identification of the variegated layers and truths of Communist documents from the colonial past and nationalist present.